Long non-coding RNA AGAP2-AS1 promotes cell proliferation and invasion through regulating miR-193a-3p/LOXL4 axis in laryngeal squamous cell carcinoma. Issue 7 (3rd April 2022) - Ren, Pengyu; Niu, Xiaorong; Zhao, Ruimin; Liu, Junsong; Ren, Wanli; Dai, Hao; Chen, Jiayu; Yan, Jinfeng; Li, Baiya; Shao, Yuan; Bai, Yanxia; Han, Peng
ABSTRACT: Laryngeal squamous cell carcinoma (LSCC) is an aggressive malignancy with highly mortality rate. Long non-coding RNA (lncRNA) AGAP2-AS1 is an identified oncogene in several types of cancers. However, the role of AGAP2-AS1 in LSCC remains unclear. The expression levels of AGAP2-AS1 in LSCC tissues and cell lines were measured using qRT-PCR. AGAP2-AS1 was knocked down in LSCC cells through transfection with siRNA-AGAP2-AS1. Cell proliferation and invasion were detected using MTT and transwell assays. Dual-luciferase reporter gene assay was performed to confirm the interaction with AGAP2-AS1 and downstream genes. Our results showed that AGAP2-AS1 expression was remarkably increased in human LSCC tissues and cell lines. Knockdown of AGAP2-AS1 significantly inhibited the proliferation and invasion of LSCC cells. In addition, AGAP2-AS1 sponged miR-193a-3p and regulated its expression in LSCC cells. Inhibition of miR-193a-3p reversed the effects of AGAP2-AS1 knockdown on LSCC cells. Furthermore, Lysyl oxidase-like 4 (LOXL4) was a target gene of miR-193a-3p and the role of miR-193a-3p was mediated by LOXL4. In conclusion, these findings suggest that knockdown of AGAP2-AS1 inhibited the proliferation and invasion of LSCC cells through regulating the miR-193a-3p/LOXL4 axis.